RELATIONSHIP BETWEEN SELECTED REPRODUCTIVE PARAMETERS OF Bagrus bayad IN KIRI RESERVOIR SHEL LENG, ADAMAWA STATE, NIGERIA - HABU, U.; VANDI , P.; CHUBADO, A. (Nigerian Journal of Fisheries, 2023)
The study is aimed at investigating the relationship between maturity stages, fecundity, length-weight relationship and condition factor of Bagrus bayad. A total of 282 samples of B. bayad were collected over a period of 6 months and the data collected from its reproductive analysis were subjected to one-way analysis of variance (ANOVA), descriptive statistic, regression analysis, graph (bar chart) mean and standard deviation were used for analyzing and presenting the data for analysis. Result from the data analysis showed the b value for male = 1.996 which is less than 3.0, hence the male fish showed a negative allometric growth pattern. While that of the female showed that the b value was 3.297 which is positive allometric growth pattern and the combined sexes analysis shows that b= 2.330, which indicated a negative allometric growth pattern. The condition factors showed that the Male has K = 2.893, Female has K = 3.122 and the Combined Sexes Condition factor is K = 3.002. Male and female gonad maturing stages is III and IV. Stage I II and VI, no fecundity for these stages and mean total fecundity ranges from 44135.18 – 90908.25. However, the increase in fecundity is related with the increase in condition factor,